The Perception of Emotions in Spoken Language in Undergraduates with High Functioning Autism Spectrum Disorder: A Preserved Social Skill. - Ben-David, Boaz M.; Ben-Itzchak, Esther; Zukerman, Gil; Yahav, Gili; Icht, Michal (Journal of Autism & Developmental Disorders, 2020)
Identifying emotions in speech is based on the interaction of lexical content and prosody. This may be disrupted in individuals with High-Functioning Autism Spectrum Disorder (HF-ASD). Undergraduates with HF-ASD (n = 20) and matched typically developed peers (n = 20) were tested using the (Hebrew) Test for Rating of Emotions in Speech. Participants rated the degree to which a target-emotion is present in spoken sentences, in which the emotional-lexical and -prosodic content appear in different combinations from trial to trial. No group differences were found in measures of emotion-identification, selective-attention (focusing on one target-channel) and integration. These preserved abilities can partially explain the high levels of independence and self-control characterizing students with HF-ASD. Support programs may rely on such skills to improve social interactions.